Program Konseling Karir pada Mahasiswa Fakultas Hukum di Universitas Syiah Kuala Banda Aceh - Aidina, Wenny; Rani, Cut Athika; Rahmah, Siti; Fauzi, Rezki; Hanifah, Rulia; Riadhah, Cut Aya; Dewi, Rini Liana; Mawarpury, Marty (Yayasan Daarul Huda Kruengmane, 2024)
Law students at Syiah Kuala University (USK) face significant challenges in planning their careers, mainly due to a lack of understanding of career opportunities in the legal field and limited access to career counseling services. This condition often results in uncertainty in career decision-making, which has an impact on anxiety and academic performance. This community service activity aims to provide a solution through the implementation of a structured career counseling program. The method used is descriptive quantitative research which includes individual counseling sessions and assessments using inventory tests, in the form of The Student Career Construction Inventory (SCCI), Self-Reporting Questionnaire (SRQ) and Color Personality Test. The results of this community service activity indicate that some students gain increased knowledge and understanding related to the career they want to achieve. In addition, there are mental health conditions and personalities that also show a relationship with the need for career counseling in students.